Synergistic effect on antioxidant activity of vitamin C provided with acidic vesiculation of hybrid fatty acids. (October 2021) - Liu, Huan; Meng, Xinyu; Li, Lei; Hu, Xueyi; Fang, Yun; Xia, Yongmei
Graphical abstract: Highlights: Conjugated linoleic acid and saturated fatty acids (SFA) vesiculated in acidic pH. The SFA induced larger and thicker vesicles, in positive relation with their chain length. SFA improved the encapsulation efficiency and sustain release of VC. The encapsulated VC exhibited dramatically higher antioxidant activity and stability. Abstract: Vitamin C has often been applied in capsule due to its sensitivity to oxygen, and it is only stable at acidic conditions; although most encapsulation of vitamin C has been carried out in neutral environment. Herein, hybrid fatty acid vesicles were constructed from conjugated linoleic acid (CLA) and saturated fatty acids (SFA) to encapsulate vitamin C in aid of sodium dodecyl sulfate under acidic conditions, with significantly improved encapsulation efficiency and sustain release of VC. The CLA-SFA and the encapsulated VC synergistically presented dramatic higher antioxidant activity in positive relation with chain length of the SFA. The possible mechanism that the SFA improved encapsulation was proposed. The SFA made larger and thicker vesicles, and the enhancement was in positive relation with chain length of the SFA, although SFA slightly broadened the vesiculation pH windows towards alkaline direction. Meanwhile, the prepared hybrid fatty acid vesicles presented good stability at room temperature.